Relatório Anual de Gestão em Saúde: aspectos para uso como instrumento de planejamento, avaliação de política de saúde e prestação de contas - Paixao, Alex Sandro da (2024)
Government control bodies, DENASUS, CGU and TCU, indicate a lack of monitoring and analysis of the Annual Health Management Reports (RAGs) of various entities by the federal manager, with a low use of RAGs as a planning and accountability instrument. Thus, taking as a reference good planning practices, the principles and guidelines of public governance, the implementation and monitoring phases of public policy, and considering the political analysis model proposed by Dye (2011), interest group model, in this study , based on research outlined in a field study, qualitative in terms of its approach, applied in terms of its purpose, descriptive and exploratory in terms of its objectives, applying bibliographic and documentary research techniques and the use of a questionnaire to the studied public, the real use of RAG’s from Municipalities and States in the planning and evaluation of health policies as well as the accountability of federal resources from the Ministry of Health (MS) is discussed, from the perspective of agents from the MS and agents from Municipal Health Departments of various federated entities, which carry out or should carry out planning, accountability, implementation, monitoring or evaluation of health actions, control and auditing activities in health, which are associated with the RAG theme, within the scope of the structure of power and competencies of health bodies and the forms of association found between them. In this way, the objective is, by discussing and highlighting the main aspects to be observed regarding the use of RAG’s, to contribute to the macro-process of evaluation, accountability and health planning, with a view to good public health governance and adequate adoption of SUS policies at national and regional level for the benefit of society. As a result, several factors and reasons have negatively influenced the planning and accountability cycle in the SUS, such as little or only basic training provided by the local body or the MS to the responsible public agents; little or only basic care regarding the standardization of result indicators; little or only basic feedback provided by the MS; little or only basic consideration of health peculiarities and regional characteristics; no, little or only basic use of the results demonstrated in the federated entity’s health RAG to carry out strategic alignment and adjust health planning; little or only basic level of establishment of internal control mechanisms and measures by health bodies, among others. Thus, as a proposition, there is an urgent need for adaptation in the macroprocess related to the health RAG that includes greater integration of work and cooperation between the control bodies themselves, including social control, and bodies that directly execute health policy, in addition to the effective incorporation of governance principles, strategic planning alignment, effective adoption of risk management principles and methods by managers and compliance with heuristic steps – planning, implementing, controlling and evaluating in a cyclical manner.